Bioadhesive and antioxidant hydrogel by MoS2-TA dual-catalytic system initiated free radical polymerization combined with phototherapy for cartilage regeneration - Qingbing Jiang; Yifeng Shang; Hong Cheng; Jinmin Zhao; Lerong Yang; Zhenzhen He; Jiyong Wei; Ruiming Liang; Wei Su; Li Zheng; Chuanan Liao (Materials Today Bio, 2025)
Tissue engineering has been used as a potential treatment strategy for articular cartilage regeneration, but current hydrogel scaffolds often fail to meet these criteria due to weak mechanical strength and unfavorable biocompatibility. Inspired by the metal ion-polyphenol redox system-initiated free radical polymerization (MPi-FRP), a novel molybdenum disulfide-tannic acid (MoS2-TA) dual-catalytic system was used as an initiator for the free radical polymerization of methacrylated hyaluronate (HAMA) to synthesize a HAMA-MoS2-TA (abbreviated as HAMA-M) nanocomposite hydrogel for cartilage repair under mild conditions. Compared to the pure HAMA hydrogel, HAMA-M hydrogels exhibited robust mechanical properties, and the adhesive strength was promoted for 81.32 %. Moreover, MoS2-TA endowed the hydrogel with excellent SOD and CAT-mimic activities and prominent photothermal conversion efficiency. Assisted by the mild photothermal therapy, the antioxidant HAMA-M hydrogel had excellent biocompatibility and effectively promoted chondrogenic differentiation of bone marrow mesenchymal stem cells by decreasing excessive ROS production, restoring mitochondrial function and promoting mitochondrial production. Further, the HAMA-M hydrogel alleviated the pro-inflammatory microenvironment and accelerated cartilage regeneration, with the ICCS score promoted to 77.75 % after 8-week therapy in vivo. This study provides a novel way for fabricating tissue engineering scaffolds and throws new light for cartilage repair.